AGGRESSIVENESS AND SCHOOL: INTERVENTION PROJECT LED BY TEACHERS - Wiezzel, A. C. S. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2020)
The article is about an action research, carried out with 36 teachers from a town of the state Sao Paulo-SP, that aimed building projects that could solve a problem related to aggressive manifestations in the classroom. Reports, questionnaires, materials that were produced in classrooms (reports, portfolios, activities performed by children) and photos were used as data collection instruments. After carrying out technical work related to child aggressiveness involving the researcher and teachers, the ladder planned the projects, developed them in classrooms and assessed their impacts on the interpersonal relationships of the children involved. The results showed active participation of teachers throughout the research process, with significant transformations identified in everyday life in the classrooms with regard to interactions between children.
Keywords: aggressiveness; intervention; teachers; child education